2011
DOI: 10.3354/meps09196
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic oxygen flux by Macrocystis pyrifera: a mass transfer model with experimental validation

Abstract: The present paper elaborates the development of a mass transfer model to determine rates of photosynthetic oxygen flux from the giant kelp Macrocystis pyrifera in a moving fluid. The model can be used to calculate local dissolved oxygen flux, blade-averaged oxygen flux and daily average net primary productivity for a kelp forest. Predicted rates of photosynthetic oxygen flux agree well with previously reported direct measurements. This model was derived from the fundamental principles of conservation of mass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The flow characteristics in the different regimes were determined in the middle of the flume using a field 10 MHz Acoustic Doppler Velocimeter (Sontek, San Diego, CA, USA) before the start of the experiment. These velocities were chosen because they represent speeds at which the DBL can reach maximal and minimal values (Hansen, Hondzo, & Hurd, ), and they are similar to those observed within kelp beds in the field (Gaylord et al., ; Jackson & Winant, ; Kregting et al., ). Individual kelp blades colonized or not by bryozoans were randomly assigned to the different flow treatments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow characteristics in the different regimes were determined in the middle of the flume using a field 10 MHz Acoustic Doppler Velocimeter (Sontek, San Diego, CA, USA) before the start of the experiment. These velocities were chosen because they represent speeds at which the DBL can reach maximal and minimal values (Hansen, Hondzo, & Hurd, ), and they are similar to those observed within kelp beds in the field (Gaylord et al., ; Jackson & Winant, ; Kregting et al., ). Individual kelp blades colonized or not by bryozoans were randomly assigned to the different flow treatments.…”
Section: Methodsmentioning
confidence: 99%
“…These velocities were chosen because they represent speeds at which the DBL can reach maximal and minimal values (Hansen, Hondzo, & Hurd, 2011), and they are similar to those observed within kelp beds in the field (Gaylord et al, 2007;Jackson & Winant, 1983;Kregting et al, 2011). Individual kelp blades colonized or not by bryozoans were randomly assigned to the different flow treatments.…”
Section: Experimental Designmentioning
confidence: 99%
“…Similarly, from measurements reported in Hansen et al . [, Table ], u*0.07U for the kelp Macrocystis pyrifera . For nearly all conditions the turbulent boundary layer model over‐predicted the measured K , and it failed to capture the trend at the higher velocity range (Figure ).…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have suggested that Turbulent KE may influence nutrient uptake (Anderson and Charters ; Koch ), and the total energy parameter captures this influence. Specifically, when Turbulent KE is weak, flux is controlled by the time‐mean diffusive sublayer thickness, which is a function of the time‐mean velocity (e.g., Hansen et al ; Rominger and Nepf ; Lei and Nepf ). However, when the Turbulent KE is high, periodic disturbances of the diffusive sublayer by the turbulence can create instantaneously higher concentration gradients at the surface and, thus, higher flux (e.g., Stevens and Hurd ; Huang et al ; Rominger and Nepf ).…”
Section: Discussionmentioning
confidence: 99%